HERBAL MEDICINES USED BY BAPEDI TRADITIONAL HEALERS TO TREAT REPRODUCTIVE AILMENTS IN THE LIMPOPO PROVINCE, SOUTH AFRICA - Semenya, S S; Maroyi, A; Potgieter, M J; Erasmus, L J C (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The current study focussed on documenting the ethnobotanical knowledge of herbal medicines used by the Bapedi traditional healers to treat reproductive ailments in the Limpopo Province, South Africa. Fifty one healers from 17 municipalities covering Capricorn, Sekhukhune and Waterberg districts of the Limpopo Province were interviewed between January and July 2011. Semi-structured interviews, observations and guided field surveys with the healers were employed. Thirty-six medicinal plant species belonging to 35 genera and 20 families were documented. The most used species were Zanthoxylum humile (25.5%), Catha edulis (21.6%), Ozoroa sphaerocarpa (15.7%), Hypoxis hemerocallidea (13.7%), Hypoxis obtusa (11.7%), Gomphocarpus fruticosus subsp. fruticosus and Gymnosporia senegalensis (9.8% each). The dominant growth forms among the reported medicinal plants were herbs (39%), followed by shrubs and trees with 33% and 28%, respectively. The preferred plant parts were roots (63.9%), followed by bark (13.9%), whole plant (11.1%), tubers (8.3%), bulbs (5.6%), fruits, leaves, stems and twigs (2.8% each). The majority of the species were used to treat gender specific reproductive ailments; while a minority were used for treating reproductive ailments of both genders. Twenty-two species (61.1%) are supported by reports of similar uses in other countries or have proven biological activity. This study illustrates that Bapedi traditional healers possess remarkable knowledge on medicinal plants used for treating and managing reproductive ailments.